Essays in Macroeconomics - Athanasopoulos, Angelos (Trinity College Dublin. School of Social Sciences & Philosophy. Discipline of Economics, 2023)
This dissertation is a collection of three essays in empirical macroeconomics. Chapter 1 examines the long-run effects of central bank independence on inflation. Applying a dynamic panel strategy to account for the persistence of inflation the chapter shows that improvements in central bank independence have a larger effect on inflation in the long-term, as compared to the short-term. The analysis shows that these effects are more significant in developing countries. The chapter also provides causal evidence of the effects of central bank reform by applying a doubly robust propensity score weighted estimation as well as an instrumental variables approach. The conclusions of the first chapter is that central bank independence plays an important role in lowering inflation in the long-term, particularly in developing countries. Chapter 2 provides novel evidence of the medium-term relationship between central bank independence and government debt. The analysis shows that central bank independence and reform are associated with an increase of government debt and a fall of the interest rate on the debt. These effects are pronounced for developing countries. The chapter interprets the evidence as suggesting that central bank independence increases fiscal space. The chapter also provides evidence that increased central bank independence lowers the pro-cyclicality of fiscal policy for developing economies, thus allowing countries to ?graduate? from emerging economy status to a developed economy one. Chapter 3 is interested in the causes and consequences of zombie firms. The chapter provides evidence of a collateral channel for the misallocation of credit. These findings are then related to the zombie congestion spill-over effects literature and it is argued that the negative spill-over effects of zombies in the literature are, at least partially, related to the role of collateral in lending. The claim in this chapter is that zombie lending is due to a commitment problem for lenders who cannot credibly commit ex ante not to refinance ex post in the presence of sunk costs. Evidence provided in the chapter shows that the stronger the effective creditor rights protection is in a country the higher the available leverage that firms can obtain, and the more serious the adverse selection ex ante is. Therefore the zombie firms problem can be traced back to an excessive build-up of leverage facilitated by a bank-based system excessively reliant on collateralisation.
APPROVED
Keywords: Central Bank independence; Inflation; Government debt